Copper Deficiency in the Lungs of TNF-α Transgenic Mice - Liu, Liu; Geng, Xiangrong; McDermott, Joseph; Shen, Jian; Corbin, Cody; Xuan, Stephanie; Kim, Jae; Zuo, Li; Liu, Zijuan (Frontiers in Physiology, 2016)
Tumor necrosis factor (TNF)-α is a well-known pro-inflammatory cytokine. Increased expression of Tnf-α is a feature of inflammatory lung diseases, such as asthma, emphysema, fibrosis and smoking-induced chronic obstructive pulmonary disease (COPD). Using a mouse line with lung-specific Tnf-α overexpression (SPC-TNF-α) to mimic TNF-α-associated lung diseases, we investigated the role of chronic inflammation in the homeostasis of lung trace elements. We performed a quantitative survey of micronutrients and biometals, including copper (Cu), zinc (Zn) and selenium (Se), in the transgenic mice tissues. We also examined the expression of Cu-dependent proteins in the inflammatory lung tissue to determine whether they were affected by the severe Cu deficiency, including cuproenzymes, Cu transporters and Cu chaperones. We found consistent lung-specific reduction of the metal Cu, with a mean decrease of 70%; however, Zn and Se were unaffected in all other tissues. RT-PCR showed that two Cu enzymes associated with lung pathology were downregulated: amine oxidase, Cu containing 3 (Aoc3) and lysyl oxidase (Lox). Two factors, vascular endothelial growth factor (Vegf) and focal adhesion kinase (Fak), related with Cu deficiency treatment, showed decreased expression in the transgenic inflammatory lung. We concluded that Cu deficiency occurs following chronic TNF-α-induced lung inflammation and this likely plays an essential role in the inflammation-induced lung damage. These results suggest the restoration of lung Cu status as a potential strategy in both treatment and prevention of chronic lung inflammation and related disorders.